Investigation of a Middle School Preservice Teacher’s Knowledge of Content and Students - Ebru Ersarı (International Journal of Assessment Tools in Education)
The purpose of this study was to explicate one preservice middle grades mathematics teacher’s Knowledge of Content and Students (KCS) in the context of multiple solution strategies. This study’s purpose is to underline the importance of preservice teachers’ KCS and provide possible investigative methods for evaluating preservice teachers’ KCS. Specifically, the research inquiry guiding this study focused on how a middle school preservice mathematics teacher displays KCS when engaging with tasks about pattern recognition and linear functions in the context of multiple solution strategies. The data consisted of three videotaped semi-structured interviews with the preservice mathematics teacher as well as the written work she produced during the interviews. This study explicated one preservice mathematic teacher’s performance regarding two important themes of KCS: generating multiple possible solution strategies of middle school students and explaining multiple student solution strategies. In terms of generating multiple solution strategies of middle school students, the study found that the preservice mathematics teacher provided the same solution strategies that she employed when she solved the problems by herself. Regarding explaining multiple student solution strategies, this study revealed that the preservice teacher did not explicate how typical middle school students reason. The preservice teacher had limitations when explaining the possible procedures that students might have used to solve problems when given the final student solutions. With regard to the teacher’s abilities to recognise and understand students’ typical understandings and misunderstandings, the study demonstrated that the preservice teacher was capable of explaining some solution strategies but not all of them.